Employment attributes of fast food service workers and their job commitment - Sanchez, Teresita T.
This study was undertaken to determine if there exists relationships between some extrinsic employment attributes and job satisfaction, as influenced by the respondents socio-economic characteristics and their plans for educational upgrade. It was conducted among 200 fast food service workers in selected 2 multinational franchises, and 2 locally-owned fast food companies in Metro Manila using a questionnaire as its survey tool. Companies were chosen based on the number of outlets and the number of employees they usually employ per outlet which averaged between 60-120. The companies selected were those that use TV, radio and print advertising, and carry similar menu offerings, with hamburger as the basic food product. Only rank and file employees called crew who work in the service counter, production and clean-up or utility services were chosen as respondents. They were asked about some employment attributes and their perception and relative satisfaction on them. They were also asked about their current socio-economic status; educational status and future plans for educational upgrade; and, their level of job commitment or desired job stay as expressed in the length of time they further intend to stay with the company. Attitudes towards selected employment attributes such as pay; fringe benefits; tenure; promotion; working conditions; length of service; nature of firm and supervision were measured using a 5-point scale of Likert type. Sub-variables were likewise measured. Data were analyzed using descriptive and inferential statistical treatment. For the descriptive analysis, frequencies and percentages were used all throughout and mode scores were used for nominal responses while mean scores were used for ranked responses. For the inferential results, stepwise logistic regression to test correlations and select predictors among variables using Biomedical Data Program (BMDPLR)- Logistic regression at .10 P level of significance was use as the main tool of analysis for efficiency and faster results. A manual rest of goodness fit using chi-square was done specifically to test sampling bias on the satisfaction attitudes towards employment attributes based on frequency distribution. Findings revealed that among the employment attributes included in the study, only tenure, salary, medical fringe benefits and promotion were found to be highly significant and were therefore entered as predictors within 10 P level of significance. Other attributes such as fringe benefits, nature for firm, supervision, length of service and their sub-variables were also found to be correlated, but not within significant level. None showed 0 or -1 log values which would show that there is no relationship at all. Results showed the ranking of employment attributes and sub-attributes as follows: 1. Salary; 2. tenure; 3. medical fringe benefits; 4. promotion, as predictors; Non predictors were: 5. company's financial stability; 6. social/ recreational fringe benefits; 7. rapport of supervisor; 8. educational fringe benefits; 9. length of service; 10. financial fringe benefits; 11. employee concern; 12. quality of supervision; 13. prestige; 14. physical working conditions; 15. adequacy of supervision;; and 16. hours and shift working conditions. While satisfaction variables for pay, tenure, fringe benefits, promotion and supervision were found to be correlated to job commitment, only satisfaction towards working conditions came out as a significant predictor of job commitment. Other variables that were found to be correlated but non-predictors were: 2. family members with jobs; 3. experience; 4. family members; 5. sex; 6. previous trainings, and 7. plan for future educational upgrade. Evaluation of the logistic regression model were made at each stepping process, accounting for the change in log-likelihood since the previous step, using thee goodness of fit x^2 statistics. A simple goodness of fit using expected and observed frequencies were manually done to know whether there was normalcy and homogeneity in the sampling, thereby pointing possible bias on satisfaction variables. Among satisfaction variables however, only satisfaction on promotion and supervision showed no normalcy or biased results on sampling. This is because not everybody had been promoted and varying satisfaction for supervision showed no homogeneity or variations of responses per company. However, the differences at 0.10 p-level of significance were minimal.